New analytical forms of a deuteron wave function for potentials of the Nijmegen group - V. I. Zhaba (Ядерна фізика та енергетика)
To approximate the deuteron wave function in coordinate representation, two new analytical forms were proposed. They are represented as the product of the power function rn for the sum of exponential terms Ai⋅exp(-ai⋅r3). For realistic phenomenological potentials of the Nijmegen group these forms are constructed as deuteron wave function in the coordinate representation, which do not contain superfluous knots. The calculated parameters of the deuteron are compared with experimental and theoretical data.